Hemophagocytic lymphohistiocytosis/cytokine release syndrome secondary to neoadjuvant pembrolizumab for triple-negative breast cancer: a case study - Patton, Laura; Monteith, Bethany; Heffernan, Paul; Herzinger, Thomas; Wilson, Brooke E. (Frontiers in Oncology, 2024)
As indications for immune checkpoint inhibitors for breast cancer continue to expand, rare toxicities will emerge that require careful consideration and multidisciplinary management. We report the case of a 40-year-old female receiving neoadjuvant pembrolizumab and chemotherapy for locally advanced triple-negative breast cancer who developed cytokine release syndrome (CRS)/hemophagocytic lymphohistiocytosis (HLH). CRS/HLH secondary to pembrolizumab are scarcely documented in the literature and, to our knowledge, have never been reported in the context of neoadjuvant treatment for breast cancer.